ANTIOXIDANT ACTIVITY DUAL METHODS OF DIFFERENT POLARITY EXTRACTS OF STEM OF SOLANUM NIGRUM L. GROWING IN ALGERIA - IMANE GUEDIRI; CHERIFA BOUBEKRI; OUANISSA SMARA (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The purpose of this study is to evaluate the antioxidants properties and phenolic and flavonoid contents of Solanum nigrum L. growing in El-Oued region (south east of Algeria). The different polarity extracts chloroform (CHCl3), ethyl acetate (AcOEt) and n-butanol (n-BuOH) have been prepared from the aqueous ethanol extract of the stem. The antioxidant activity of extracts was determined by DPPH (2, 2-diphenyl-1-picrylhydrazyl), FRAP (Ferric ion reducing antioxidant power) assays. The results showed that CHCl3 extract has the highest level of polyphenol (66.427 ± 0.001 mg gallic acid / g) while, the AcOEt extract has the highest level of flavonoid content (26.450 ± 0.079 mg rutin equivalents / g). In addition, the highest IC50 of DPPH scavenging activity has exhibited the most potent antioxidant capacity assay of CHCl3 (0.231 mg∙mL-1) compared to the n-BuOH and AcOEt extracts. Furthermore, the highest value of FRAP for AcOEt extract was 458.291 ± 0.005. In this study, it has been noted that the potency of the antioxidant activity of DPPH may be identified through different levels of polyphenol. However, the value of FRAP has a relation to the value of flavonoid.